Efektifitas Peran Kader Terhadap Motivasi Ibu Mengikuti KB IUD Di Desa Karangrejo Kecamatan Blimbingsari Kabupaten Banyuwangi Jawa TimurEfektifitas Peran Kader Terhadap Motivasi Ibu Mengikuti KB IUD Di Desa Karangrejo Kecamatan Blimbingsari Kabupaten Bany: The Effectiveness of Cadre Roles on Mother's Motivation to Participate in IUD Family Planning in Karangrejo Village, Blimbingsari District, Banyuwangi Regency, East Java - Hakiki, Miftahul; Kurniawati, Indah; Hariyani, Wahyu Fuji (Jurnal Kebidanan Midwiferia, 2019)
The number of long-term Intra Uterine Device (IUD) family planning acceptors in Karangrejo village, Blimbingsari is still low for about 37%. The purpose of this study was to analyze the effectiveness of the cadres’ role on mothers’ motivation in using IUD family planning program. The research type was a cross sectional study with one group pre-post test design. The population was productive aged mothers in Karangrejo Village, Blimbingsari, Banyuwangi. The sample taken was some of the productive aged mothers in Karangrejo Village, Blimbingsari, Banyuwangi. The sample was taken by using purposive sampling technique. The analysis technique used Wilcocson Test. The research results before the mothers got motivation on the use of IUD contraception, there were 51 (59.3%) respondents used IUD contraception, it was categorized as less. After getting motivation, there were 57 (66.2%) respondents used IUD contraceptives, it was categorized as good criteria. The results of data analysis by Wilcoxon test using SPSS for Windows 23 showed that Sig (P) = 0.00 <0.05, So Ho was rejected, it means that there was correlation between the effectiveness of cadres’ role on mothers’ motivation in using IUD family planning program in Karangrejo village, Blimbingsari, Banyuwangi in 2019. From this study, it can be concluded that the activeness of cadres in giving motivation to the productive aged mothers give good result. Many productive aged mothers want to use IUD contraception in the near future.